Firms’ speed of adjustment and rational financing behaviour: Malaysian evidence - Haron, Razali (2014 Inderscience Enterprises Ltd. , UK, 2014)
Malaysian firms which are examined based on a dynamic framework appear to practice target capital structure and take into account certain firm characteristics in their capital structure decisions. These firms readjust instantaneously when they are off the target indicating low adjustment cost while the pecking order hypothesis seems to influence the financing decisions. Found to be over-levered most firms behave rationally by cutting down the amount of debt in their capital structure to reach the target. In terms of the proximity to the target, under-levered firms are found to be much closer to target than over-levered firms. This study contributes to the literature by identifying the rational financing behaviour and the proximity of Malaysian firms to target leverage. This indication of firms’ proximity to target can help managers to outline and set the next steps to be taken in order to reach the target capital structure to maximise firm value.